2D MoN‐VN Heterostructure To Regulate Polysulfides for Highly Efficient Lithium‐Sulfur Batteries. Issue 51 (7th November 2018) - Ye, Chao; Jiao, Yan; Jin, Huanyu; Slattery, Ashley D.; Davey, Kenneth; Wang, Haihui; Qiao, Shi‐Zhang
Abstract: Lithium‐sulfur batteries hold promise for next‐generation batteries. A problem, however, is rapid capacity fading. Moreover, atomic‐level understanding of the chemical interaction between sulfur host and polysulfides is poorly elucidated from a theoretical perspective. Here, a two‐dimensional (2D) heterostructured MoN‐VN is fabricated and investigated as a new model sulfur host. Theoretical calculations indicate that electronic structure of MoN can be tailored by incorporation of V. This leads to enhanced polysulfides adsorption. Additionally, in situ synchrotron X‐ray diffraction and electrochemical measurements reveal effective regulation and utilization of the polysulfides in the MoN‐VN. The MoN‐VN‐based lithium‐sulfur batteries have a capacity of 708 mA h g −1 at 2 C and a capacity decay as low as 0.068 % per cycle during 500 cycles with sulfur loading of 3.0 mg cm −2 . Abstract : V for victory : A two‐dimensional MoN‐VN heterostructure is investigated as a model sulfur host. The heterostructure can regulate polysulfides and improve sulfur utilization efficiency, resulting in superior rating and cycling performance. More importantly, incorporation of V in the heterostructure can effectively tailor the electronic structure of MoN, leading to enhanced polysulfides adsorption.